Mechanism of Transformational Leadership on Team Performance and Recommended Interventions on AI-Lab - Zhuofeng Li (International School for Social and Business Studies, 2023)
Purpose: The purpose of this study is to synthesize the relationships between transformational leadership and the intermediate outcomes (e.g., team vision, team coordination, team cohesion, team project innovation) of team performance, then to propose relevant interventions to enhance the team performance of the case setting. Study design: Based on the empirical literature review, this study employs the case study method to incorporate relevant transformational behaviors and techniques into the practical issues of the case setting. Findings: This study demonstrates the positive relationships between the 4I's of transformational leadership and the intermediate outcomes of team performance, and finds some unique transformational techniques to cope with the managerial problems during business transition. Originality/value: This study contributes to formulating an original theoretical framework on transformational leadership and team performance, and employing a series of exclusive intervention measures to improve the team performance of the case setting. The contributions may generalize into the wider education service sector.